(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Electronic advertising is a sophisticated means of communication that keeps pace with the times and ease of access to the recipient in a way that suits communication technical developments and human trends. On the effect on the recipient through the content of the suggestive metaphor, which depends on the juxtaposition of two content, each of which carries a hypothetical significance to the content of the advertisement, as the metaphor is represented by two meanings, the first for the real image, and the second for the relational construction according to the designer’s vision to form a hypothetical design building within the the formality metaphor that the designer invents in Advertisement works within a technical formula that is adequate and influential in the recipient, and from this point of view, the research problem raised by the two researchers is summarized in the following questions : - How is the hypothetical metaphor structured in electronic advertising? - What are the outcomes of the hypothetical construction of the formality metaphor in electronic advertising and its communicative effectiveness? The importance of the research lies in the fact that it establishes intellectual and applied premises for the axes of The virtual structure and the formality metaphor, in addition to that it is a scientific method in employing virtual the formality metaphor in electronic advertising. The current research aims to reveal the mechanisms of employing the hypothetical construction of the formality metaphor in electronic advertising..